The Role of State Aid in the COVID-19 Pandemic – Polish Case Study - Zygała, Julia; Gutierrez Bartoszewski, Marcel (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The article aims to assess the utility of the legal instruments implemented during the COVID-19 pandemic in terms of responding to other sudden crises with vast economic consequences. The analysis will consist of presenting the legal basis for state aid, the measures undertaken and their consequences on both the EU and national level. Firstly, the legal response to the crisis on the EU level will be tackled with a particular focus on the provisions of the temporary framework. Other possible legal bases will also be taken into consideration – Article 107(2)b TFEU, Article 107(3)c TFEU, de minimis regulation, General Block Exemption Regulation. Secondly, the response to the crisis in Poland will be analysed on two levels: legislation (implementation of the “anti-crisis shield”) and jurisprudence (using the example of the judgement of the Administrative Court in Opole I SA/Op 97/21 from April 23, 2021, which resolved the legal controversies regarding the so-called PKD classification).